President's Message - Socha, Linda (Operating Room Nurses Association of Canada Journal, 2008)
In a previous President’s Message I discussed the subject of patient safety and the fact that creating a culture of safety is every health care provider’s responsibility. ORNAC continues to be actively involved in several patient safety initiatives of which the most recent and farreaching is the World Health Organization’s (WHO) Safe Surgery Saves Lives Challenge.